Work-life balance in nurses working in hospital: a model with the mediating role of emotional intelligence - Saeed Amini Moghaddam; Alireza Manzari Tavakoli; Sanjar Salajegheh; Samaneh Mehdizadeh; Zahra Shokoh (Shahid Beheshti University of Medical Sciences, 2022)
Background: The aim of this study was to investigate the balance of work and life with the role of mediation of emotional intelligence in nurses working in hospitals in Kerman University of Medical Sciences. Methods: This study was a descriptive and correlational research. The method of data collection was a combination of library and field studies and the tools of data collection were a review of documents, interviews and researcher-made questionnaires, including work-life balance factors and emotional intelligence questionnaire. The population included all 2740 nurses, who were working in hospitals of Kerman University of Medical Sciences. 508 people were selected by using a stratified sampling method, SPSS-23 and AMOS-24 software was used to analyze the data. Results: The research results showed a significant relationship between work-life balance factors and emotional intelligence. It showed that by improving the implementation of work-life balance factors, the conditions for increasing emotional intelligence are provided. Based on the coefficient of determination (R2), 51% of the changes in emotional intelligence were explained by factors related to work-life balance. The rate of direct effect was estimated to be 0.714 and the rate of indirect effect through emotional intelligence was estimated to be 0.333. Conclusion: The organization should help nurses to achieve the necessary capability and conditions, facilities, and welfare so that the nurses could work in an environment in which a balance between work and family responsibilities is established.